PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN SOCIOSCIENTIFIC ISSUES TERHADAP LITERASI SAINS SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Siregar, Silvia Ardina; Kurniawan, Fery; Rizkiyahnur Nasution, Wilda; Sukarwati, Rumini (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2025)
The study aims to determine the effect of the problem-based learning model with the socioscientific issues approach on students' science literacy on environmental pollution materials. Learning models that have not involved students' activeness in learning cause students' science literacy to be underdeveloped. In addition, learning materials that do not connect social issues or social issues make the material less relevant in daily life. The method used in this study is a quasi-experimental method. The data collection technique uses an essay question test containing 15 valid and reliable questions. The results of the normality test research use the shapiro wilk formula by using spss application the homogeneity test use the lavene test and the hypothesis test using an independent simple t-test. The results of the hypothesis test after analyzing the data show ttabel about 3.670 and the t tabel is 0.254 with a significant level of α = 0.05. Based on decision-making, the t-test on the bound variable is not greater than the alpha value, which is 0.05, so h0 and ha are accepted. Therefore, it is stated that the results of the study show how the problem-based learning learning model with the socioscientific issues approach has an effect on students' science literacy in environmental pollution material in grade x students of sma negeri 5 padangsidimpuan.